Development of RADEC Based E-Modules Integrated with SETS Approach to Green Chemical Materials - Nilawati Nilawati; Mauliza Mauliza; Coryna Oktaviani (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This research is motivated by the lack of interactive teaching materials integrated with learning models and approaches in green chemistry materials. One potential solution is the development of E-Modules based on the RADEC learning model, integrated with the SETS approach to green chemistry materials. This study aims to analyze the needs, feasibility, practicality, and students' responses to the E-Modules developed. This research is a development research with the ADDIE model. The instruments used are the interview sheet, needs questionnaire, material expert and media expert validation sheet, practicality questionnaire, and learner response questionnaire. The subjects of this study consisted of chemistry teachers and students at SMA Negeri 2 Langsa, SMA Negeri 3 Langsa, and SMA Negeri 5 Langsa. The results of the needs analysis showed 71.43% in the needed category, validation by material and media experts, with Aiken's V scores of 0.91 and 0.95, respectively, both very valid; practicality of 90.40% in the convenient category; and student response of 88.43% in the exciting category. Thus, the RADEC-based E-Module, integrated with the SETS approach to green chemistry materials, is highly feasible as a teaching resource in schools.